Adjuvant chemoradiotherapy versus radiotherapy alone for women with high-risk endometrial cancer (PORTEC-3): final results of an international, open-label, multicentre, randomised, phase 3 trial. Issue 3 (March 2018) - de Boer, Stephanie M; Powell, Melanie E; Mileshkin, Linda; Katsaros, Dionyssios; Bessette, Paul; Haie-Meder, Christine; Ottevanger, Petronella B; Ledermann, Jonathan A; Khaw, Pearly; Colombo, Alessandro; Fyles, Anthony; Baron, Marie-Helene; et al.
Summary: Background: Although women with endometrial cancer generally have a favourable prognosis, those with high-risk disease features are at increased risk of recurrence. The PORTEC-3 trial was initiated to investigate the benefit of adjuvant chemotherapy during and after radiotherapy (chemoradiotherapy) versus pelvic radiotherapy alone for women with high-risk endometrial cancer. Methods: PORTEC-3 was an open-label, international, randomised, phase 3 trial involving 103 centres in six clinical trials collaborating in the Gynaecological Cancer Intergroup. Eligible women had high-risk endometrial cancer with FIGO 2009 stage I, endometrioid-type grade 3 with deep myometrial invasion or lymph-vascular space invasion (or both), endometrioid-type stage II or III, or stage I to III with serous or clear cell histology. Women were randomly assigned (1:1) to receive radiotherapy alone (48·6 Gy in 1·8 Gy fractions given on 5 days per week) or radiotherapy and chemotherapy (consisting of two cycles of cisplatin 50 mg/m 2 given during radiotherapy, followed by four cycles of carboplatin AUC5 and paclitaxel 175 mg/m 2 ) using a biased-coin minimisation procedure with stratification for participating centre, lymphadenectomy, stage of cancer, and histological type. The co-primary endpoints were overall survival and failure-free survival. We used the Kaplan-Meier method, log-rank test, and Cox regression analysis for final analysis by intention to treat and adjusted for stratification factors. The study was closed on Dec 20, 2013, after achieving complete accrual; follow-up is ongoing. PORTEC-3 is registered with ISRCTN, number ISRCTN14387080, andClinicalTrials.gov, numberNCT00411138 . Results: 686 women were enrolled between Nov 23, 2006, and Dec 20, 2013. 660 eligible patients were included in the final analysis, of whom 330 were assigned to chemoradiotherapy and 330 were assigned to radiotherapy. Median follow-up was 60·2 months (IQR 48·1–73·1). 5-year overall survival was 81·8% (95% CI 77·5–86·2) with chemoradiotherapy versus 76·7% (72·1–81·6) with radiotherapy (adjusted hazard ratio [HR] 0·76, 95% CI 0·54–1·06; p=0·11); 5-year failure-free survival was 75·5% (95% CI 70·3–79·9) versus 68·6% (63·1–73·4; HR 0·71, 95% CI 0·53–0·95; p=0·022). Grade 3 or worse adverse events during treatment occurred in 198 (60%) of 330 who received chemoradiotherapy versus 41 (12%) of 330 patients who received radiotherapy (p<0·0001). Neuropathy (grade 2 or worse) persisted significantly more often after chemoradiotherapy than after radiotherapy (20 [8%] women vs one [1%] at 3 years; p<0·0001). Most deaths were due to endometrial cancer; in four patients (two in each group), the cause of death was uncertain. One death in the radiotherapy group was due to either disease progression or late treatment complications; three deaths (two in the chemoradiotherapy group and one in the radiotherapy group) were due to either intercurrent disease or late treatment-related toxicity. Interpretation: Adjuvant chemotherapy given during and after radiotherapy for high-risk endometrial cancer did not improve 5-year overall survival, although it did increase failure-free survival. Women with high-risk endometrial cancer should be individually counselled about this combined treatment. Continued follow-up is needed to evaluate long-term survival. Funding: Dutch Cancer Society, Cancer Research UK, National Health and Medical Research Council Project Grant and Cancer Australia, L'Agenzia Italiana del Farmaco, and Canadian Cancer Society Research Institute.